Support Mechanism of School Administrators and Work Engagement of Teachers during the New Normal - Marcelino, San Vielle (Journal of Interdisciplinary Perspectives, 2024)
This study aims to determine the level of support mechanisms teachers received from their school supervisors during the New Normal and its impact on their work engagement. The respondents of this study are 90 teachers in Bacong District, Negros Oriental. The method used in the study is descriptive-correlational and employed a validated self-made questionnaire. Results revealed that the level of mental support teachers receive is high, while instructional and technological support levels are very high. The level of work engagement among the teachers is also high. The teaching position held by teachers is significantly and inversely related to their work engagement, indicating that the higher the teaching position held by the teacher, the lower their work engagement. Additionally, this study reveals that there is no significant relationship between the teachers' highest educational attainment, length of service, or number of training hours and their work engagement. These results underscore the importance of continued support for teachers, especially those in leadership roles, to enhance their engagement and effectiveness in the evolving educational landscape